Preparation process of nanoscale anti-condensation calcium hydroxide
Through sol-gel method and spray drying technology, combined with modified silane coupling agent treatment, the complex and agglomeration problems of nano-level calcium hydroxide preparation process are solved, and high-efficiency and low-cost nano-level calcium hydroxide preparation is achieved, which improves the Its dispersion and application performance.
Patent Information
- Application Number
- CN202411703647.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nano-scale calcium hydroxide preparation process is complex, the production price is high, and nano-calcium hydroxide is prone to agglomeration, affecting its performance and application.
The sol-gel method is used to form a nano-sized sol through the hydrolysis and condensation reaction of the precursor. Combined with spray drying and modified silane coupling agent treatment, uniform nano-sized anti-coagulation calcium hydroxide is prepared to prevent agglomeration.
The preparation process is simplified, the production cost is reduced, the dispersion and reactivity of nano-scale calcium hydroxide is improved, and it is suitable for mass production, enhancing the strength and durability of concrete.
Smart Images

Figure CN119191323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, mainly relates to calcium hydroxide, and specifically relates to a preparation process of nano-level anti-coagulation calcium hydroxide. Background Art
[0002] Nanomaterials have excellent optical, electronic, magnetic and mechanical properties due to their unique small size effects, surface effects and quantum effects, and are therefore widely used in biomedicine, catalysis, energy, environment and aerospace fields. The physical and chemical properties of nanomaterials are strongly dependent on their size, crystal form and morphology. Therefore, it is still a challenge to control the synthesis of nanomaterials with different structures and geometric configurations, such as nanowires, nanorods, nanotubes, nanobelts, etc., which also lays an important foundation for the construction of nanofunctional devices. Nanoscale anti-coagulation calcium hydroxide It is a nano material with special properties, which is widely used in building materials, environmental protection, agriculture and medicine. Due to its nano-scale characteristics, nano calcium hydroxide has a large specific surface area and high reactivity, but it is also easy to agglomerate, which affects its performance. Therefore, anti-coagulation treatment is a key step in the preparation and application of nano calcium hydroxide. Calcium hydroxide is commonly known as slaked lime and hydrated lime. With the rapid development of industrial modernization and the increasing attention of the country to environmental protection, calcium hydroxide has been widely used. For example: petrochemical industry, pharmaceutical and food industry, fine chemical industry, environmental protection field, etc., and the consumption is increasing rapidly year by year. High-quality nano anti-coagulation calcium hydroxide is even more seriously unbalanced. At the same time, with the elimination of backward production capacity and the improvement of environmental protection requirements by the country, local production and scale will gradually withdraw from the market, and the trend of supply and demand will further expand. The market has spawned calcium hydroxide production enterprises with a certain production scale and high product quality. In order to obtain nano calcium hydroxide, scholars have invented many methods. It can be roughly divided into two categories: top-down method and bottom-up method. For the former method, it mainly takes the form of crushing and grinding. However, this method is time-consuming, energy-consuming, and the yield of nano calcium hydroxide is very low. The bottom-up method is to use chemical methods to obtain nano calcium hydroxide particles through crystal growth. This method mainly includes aqueous solution method, alcohol solution method, microemulsion method, plasma metal method, ion resin exchange method, and calcium carbide and calcium metal method. Nano-scale anti-coagulation calcium hydroxide can effectively prevent agglomeration and improve its dispersibility and stability through surface modification, mechanical treatment and chemical modification. These treatment methods not only improve the performance of nano-scale calcium hydroxide, but also expand its application in building materials, environmental protection, agriculture and medicine. Nano-scale anti-coagulation calcium hydroxide ( ) generally includes the following steps: preparation of nano-scale calcium hydroxide, surface modification, mechanical treatment and drying. However, the current process for preparing nano-scale calcium hydroxide on the market is complicated and the production price is high, which is not conducive to the healthy development of the industry. Therefore, inventing a perfect process for preparing nano-scale anti-coagulation calcium hydroxide is of great significance to promote social development. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention prepares nano-scale anti-coagulation calcium hydroxide by a sol-gel method, specifically, by hydrolysis and condensation reaction of a precursor to form a nano-scale sol, and then by drying and heat treatment to obtain nanoparticles. The specific preparation steps include: S1. Take 2.2-3.4 g of sodium dodecyl sulfate (SDS), 3.1-3.7 g of sodium lauroyl sarcosinate, 4.2-4.8 g of urea, 15-20 g of sodium hydroxide and 5.1-5.4 g of sodium carboxymethyl cellulose, dissolve them in 15-22 mL of ammonia water, 8-13 mL of ethylene glycol and 125-145 mL of deionized water, and treat them by ultrasonic treatment at a temperature of 40-45 ° C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment caused by ultrasound and precise temperature control are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-scale calcium hydroxide.
[0004] S2, 18-23 g Dissolve in 105-112 mL of deionized water, 33-45 mL of ethanol and 8-11 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring, so that the precursor is hydrolyzed and condensed to form a sol, and the sol is aged at 58-75 ° C for 15-22 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0005] S3, the nanometer calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent to form a uniform suspension, and the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 3-5 mL / min to ensure the stability and uniformity of the spray drying process, and a centrifugal nozzle is selected to atomize the liquid into fine droplets by high-speed rotation, and the inlet temperature is set to 121-235 ° C, and the outlet temperature is set to 83-118 ° C, and the dried nanoparticles are obtained. Then, a cyclone separator is used to collect the dried powder, and the collected powder is sieved to remove large particles and agglomerates to ensure that the particle size of the powder is uniform, and then heat-treated, calcined at 298-485 ° C for 2-4 h to remove organic matter to obtain nanometer calcium hydroxide; finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, and quickly dry them to obtain dry nanoparticles. For nano-scale calcium hydroxide gel, this step uses spray drying to effectively maintain the dispersibility and morphology of its nanoparticles.
[0006] S4. Dissolve 8-11 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) in 53-62 mL of acetone, stir evenly, slowly add 11-13 mL of water, add 5.8-6.7 g of porphyrin calcium, continue stirring for 25-30 min, add 5-7 g of sodium citrate to adjust the pH value to 5.5-6.2 to promote hydrolysis and condensation reactions, heat the reaction mixture to 63-75°C, continue stirring for 3-4 h, and obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0007] S5, disperse 19-27 g of the nanometer-scale calcium hydroxide prepared in step S3 in 55-67 mL of ethanol, ultrasonicate for 10-30 min to ensure the effect of dispersing nanoparticles, then continue to add 22-34 mL of the modified silane coupling agent solution prepared in step S4, and stir for 2-4 h; separate the modified nanoparticles by centrifugation, wash them with ethanol for several times, and then dry them at 60-80 ° C to obtain nanometer-scale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanometer-scale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0008] Preferably: in step S1 of the present invention, 2.8 g of sodium dodecyl sulfate (SDS), 3.5 g of sodium lauroyl sarcosinate, 4.6 g of urea, 19 g of sodium hydroxide and 5.4 g of sodium carboxymethyl cellulose are dissolved in 19 mL of ammonia water, 11 mL of ethylene glycol and 135 mL of deionized water, and ultrasonically treated at 42 ° C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-scale calcium hydroxide.
[0009] Preferably: in step S1 of the present invention, 2.2 g of sodium dodecyl sulfate (SDS), 3.6 g of sodium lauroyl sarcosinate, 4.2 g of urea, 20 g of sodium hydroxide and 5.4 g of sodium carboxymethyl cellulose are dissolved in 17 mL of ammonia water, 11 mL of ethylene glycol and 135 mL of deionized water, and ultrasonically treated at 43 ° C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-scale calcium hydroxide.
[0010] Preferably: in step S2 of the present invention, 19 g of Dissolve in 112 mL of deionized water, 39 mL of ethanol and 10 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 70 °C for 19 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0011] Preferably: in step S2 of the present invention, 21 g of Dissolve in 111 mL of deionized water, 37 mL of ethanol and 9 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 68 °C for 18 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0012] Preferably: in step S3 of the present invention, the nanometer-scale calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent to form a uniform suspension, and the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 4 mL / min to ensure the stability and uniformity of the spray drying process. A centrifugal nozzle is selected to atomize the liquid into fine droplets by high-speed rotation, and the inlet temperature is set to 215°C and the outlet temperature is set to 98°C for rapid drying to obtain dried nanoparticles. The dried powder is then collected using a cyclone separator, and the collected powder is sieved to remove large particles and agglomerates to ensure that the particle size of the powder is uniform. The powder is then heat treated and calcined at 305°C for 3 h to remove organic matter to obtain nanometer-scale calcium hydroxide. Finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer-scale calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, and quickly dry them to obtain dry nanoparticles. For nano-scale calcium hydroxide gel, this step uses spray drying to effectively maintain the dispersibility and morphology of its nanoparticles.
[0013] Preferably: in step S4 of the present invention, 11 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) is dissolved in 53 mL of acetone, stirred evenly, 13 mL of water is slowly added, 6.7 g of porphyrin calcium is added, stirring is continued for 30 min, 6 g of sodium citrate is added to adjust the pH value to 6.2 to promote hydrolysis and condensation reactions, the reaction mixture is heated to 74 ° C, and stirring is continued for 3-4 h to obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0014] Preferably: in step S5 of the present invention, 25 g of the nanoscale calcium hydroxide prepared in step S3 is dispersed in 67 mL of ethanol, ultrasonically treated for 22 min to ensure the effect of dispersing nanoparticles, and then 34 mL of the modified silane coupling agent solution prepared in step S4 is added and stirred for 3 h; the modified nanoparticles are separated by centrifugation, washed with ethanol for multiple times, and then dried at 70 ° C to obtain nanoscale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanoscale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0015] Preferably: the experimental drugs described in the present invention are all purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes a sol-gel method to prepare nano-scale anti-coagulation calcium hydroxide, which is simple to operate and suitable for batch production.
[0017] 2. The nano-scale calcium hydroxide prepared by the present invention has good anti-coagulation effect.
[0018] 3. The nano-scale calcium hydroxide prepared by the present invention exhibits excellent dispersibility and reactivity due to its small size effect and high specific surface area.
[0019] 4. The present invention utilizes the cavitation effect of ultrasound during the preparation of nano-scale calcium hydroxide to destroy the van der Waals force between particles and prevent agglomeration.
[0020] 5. The nano-scale calcium hydroxide prepared by the present invention can improve the strength and durability of concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1This is a transmission electron microscopy (TEM) image of the nanoscale anti-coagulation calcium hydroxide prepared in Example 1 of the present invention.
[0022] Figure 2-Figure 4 This is a scanning electron microscope (SEM) image of the nanoscale anti-coagulation calcium hydroxide prepared in Comparative Examples 1-3 of the present invention.
[0023] Figure 5 The XRD curves of the nano-scale anti-coagulation calcium hydroxide prepared in Examples 1 and 2 of the present invention and Comparative Examples 4 and 5 are shown.
[0024] Figure 6-Figure 8 This is a scanning electron microscope (SEM) image of the nanoscale anti-coagulation calcium hydroxide prepared in Example 4 and Comparative Examples 8-9 of the present invention. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Example 1
[0026] S1. Take 2.2 g of sodium dodecyl sulfate (SDS), 3.1 g of sodium lauroyl sarcosinate, 4.2 g of urea, 15 g of sodium hydroxide and 5.1 g of sodium carboxymethyl cellulose, dissolve them in 15 mL of ammonia water, 8 mL of ethylene glycol and 125 mL of deionized water, and ultrasonically treat them at 40 °C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-calcium hydroxide.
[0027] S2, 18 g Dissolve in 105 mL of deionized water, 33 mL of ethanol and 8 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 58 °C for 15 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the already formed agglomerates through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0028] S3, the nanometer calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent, and after forming a uniform suspension, the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 3 mL / min, to ensure the stability and uniformity of the spray drying process, select a centrifugal nozzle, and atomize the liquid into fine droplets by high-speed rotation, set the inlet temperature to 121 ° C, and the outlet temperature to 83 ° C, and dry quickly to obtain dry nanoparticles, and then use a cyclone separator to collect the dried powder, sieve the collected powder, remove large particles and agglomerates, ensure that the particle size of the powder is uniform, and then heat treat, calcine at 298 ° C for 2 h to remove organic matter, and obtain nanometer calcium hydroxide; finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, dry quickly, and obtain dry nanoparticles. For the nano-scale calcium hydroxide gel, the spray drying method in this step can effectively maintain the dispersibility and morphology of its nanoparticles.
[0029] S4. Dissolve 8 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) in 53 mL of acetone, stir evenly, slowly add 11 mL of water, add 5.8 g of porphyrin calcium, continue stirring for 25 min, add 5 g of sodium citrate to adjust the pH value to 5.5 to promote hydrolysis and condensation reactions, heat the reaction mixture to 63 °C, and continue stirring for 3 h to obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0030] S5, disperse 19 g of the nanoscale calcium hydroxide prepared in step S3 in 55 mL of ethanol, ultrasonicate for 10 min to ensure the effect of dispersing nanoparticles, then continue to add 22 mL of the modified silane coupling agent solution prepared in step S4, and stir for 2 h; separate the modified nanoparticles by centrifugation, wash them with ethanol for several times, and then dry them at 60 ° C to obtain nanoscale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanoscale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0031] Comparative Example 1: Except that 2.2 g of sodium dodecyl sulfate (SDS) is not added in step S1, the remaining steps are the same as those in Example 1.
[0032] Comparative Example 2: Except that 3.1 g of sodium lauroyl sarcosinate was not added in step S1, the remaining steps were the same as those in Example 1.
[0033] Comparative Example 3: Except that urea is not added in step S1, the remaining steps are the same as those in Example 1.
[0034] Figure 1 This is a transmission electron microscopy (TEM) image of the nanoscale anti-coagulation calcium hydroxide prepared in Example 1 of the present invention. Figure 2-Figure 4 The scanning electron microscope SEM of the nano-scale anti-coagulation calcium hydroxide prepared in Comparative Examples 1-3 of the present invention. It can be seen from the figure that the nano-scale anti-coagulation calcium hydroxide prepared in Example 1 is evenly dispersed and has a stronger granular feel than that prepared in Comparative Examples 1-3. Moreover, the particle sizes of calcium hydroxide are different. It can be seen that sodium dodecyl sulfate (SDS), sodium lauroyl sarcosine and urea are indispensable for the preparation of alkali solution, and there is a certain synergistic effect between the three. The short vacuum microenvironment caused by ultrasound is quickly fragmented and dissolved in the alkali solution, thereby promoting it to play a better role in the subsequent reaction process, which is conducive to the rapid generation of nano-scale calcium hydroxide. Example 2
[0035] S1. Take 3.4 g of sodium dodecyl sulfate (SDS), 3.7 g of sodium lauroyl sarcosinate, 4.8 g of urea, 20 g of sodium hydroxide and 5.4 g of sodium carboxymethyl cellulose, dissolve them in 22 mL of ammonia water, 13 mL of ethylene glycol and 145 mL of deionized water, and ultrasonically treat them at 45 °C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-calcium hydroxide.
[0036] S2, 23 g Dissolve in 112 mL of deionized water, 45 mL of ethanol and 11 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 75 °C for 22 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0037] S3, the nanometer calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent, and after forming a uniform suspension, the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 5 mL / min, to ensure the stability and uniformity of the spray drying process, select a centrifugal nozzle, and atomize the liquid into fine droplets by high-speed rotation, set the inlet temperature to 235 ° C, and the outlet temperature to 118 ° C, and dry quickly to obtain dry nanoparticles, and then use a cyclone separator to collect the dried powder, sieve the collected powder, remove large particles and agglomerates, ensure that the particle size of the powder is uniform, and then heat treat, calcine at 485 ° C for 4 h to remove organic matter, and obtain nanometer calcium hydroxide; finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, dry quickly, and obtain dry nanoparticles. For the nano-scale calcium hydroxide gel, the spray drying method in this step can effectively maintain the dispersibility and morphology of its nanoparticles.
[0038] S4. Dissolve 11 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) in 62 mL of acetone, stir evenly, slowly add 13 mL of water, add 6.7 g of porphyrin calcium, continue stirring for 30 min, add 7 g of sodium citrate to adjust the pH value to 6.2 to promote hydrolysis and condensation reactions, heat the reaction mixture to 75 °C, and continue stirring for 4 h to obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0039] S5, disperse 27 g of the nanometer-scale calcium hydroxide prepared in step S3 in 67 mL of ethanol, ultrasonicate for 30 min to ensure the effect of dispersing nanoparticles, then continue to add 34 mL of the modified silane coupling agent solution prepared in step S4, and stir for 4 h; separate the modified nanoparticles by centrifugation, wash them with ethanol for several times, and then dry them at 80 ° C to obtain nanometer-scale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanometer-scale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0040] Comparative Example 4: Except that 6.7 g of porphyrin calcium is not added in step S4, the remaining steps are the same as those in Example 2.
[0041] Comparative Example 5: Except that sodium hydroxide is not added in step S1, the remaining steps are the same as those in Example 2.
[0042] Figure 5 The XRD curves of the nano-scale anti-coagulation calcium hydroxide prepared in Examples 1 and 2 of the present invention and Comparative Examples 4 and 5 are shown in FIG. 1 . As can be seen from the XRD graph, the peak positions of Examples 1 and 2 are located at 18.2°, 28.6°, 34.2°, 47.2°, 50.7°, 54.2°, 62.5°, 64.2° and 71.8°, respectively, corresponding to the (001), (100), (101), (102), (110), (111), (201), (103) and (202) crystal planes. This result is consistent with the The peak height of comparative example 4 is lower than that of examples 1 and 2. The calcium supplement of epiporphyrin provides sufficient Ca for the whole system. 2+In addition to ions, the molecules of calcium porphyrin in the system are conducive to better supporting and dispersing nano-scale calcium hydroxide particles. The samples prepared in comparative example 5 in the absence of sodium hydroxide all have carbon peaks, indicating that calcium hydroxide cannot be formed without sodium hydroxide. Example 3
[0043] S1. Take 2.9 g of sodium dodecyl sulfate (SDS), 3.5 g of sodium lauroyl sarcosinate, 4.5 g of urea, 19 g of sodium hydroxide and 5.2 g of sodium carboxymethyl cellulose, dissolve them in 19 mL of ammonia water, 9 mL of ethylene glycol and 129 mL of deionized water, and ultrasonically treat them at 42 °C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-calcium hydroxide.
[0044] S2, 19 g Dissolve in 109 mL of deionized water, 39 mL of ethanol and 9 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 59 °C for 19 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0045] S3, the nanometer calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent, and after forming a uniform suspension, the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 5 mL / min, to ensure the stability and uniformity of the spray drying process, select a centrifugal nozzle, and atomize the liquid into fine droplets by high-speed rotation, set the inlet temperature to 149 ° C, and the outlet temperature to 89 ° C, and dry quickly to obtain dry nanoparticles, and then use a cyclone separator to collect the dried powder, sieve the collected powder, remove large particles and agglomerates, ensure that the particle size of the powder is uniform, and then heat treat, calcine at 398 ° C for 3 h to remove organic matter, and obtain nanometer calcium hydroxide; finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, dry quickly, and obtain dry nanoparticles. For the nano-scale calcium hydroxide gel, the spray drying method in this step can effectively maintain the dispersibility and morphology of its nanoparticles.
[0046] S4. Dissolve 9 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) in 59 mL of acetone, stir evenly, slowly add 12 mL of water, add 5.9 g of porphyrin calcium, continue stirring for 29 min, add 6 g of sodium citrate to adjust the pH value to 5.9 to promote hydrolysis and condensation reactions, heat the reaction mixture to 69 ° C, continue stirring for 2 h, and obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0047] S5, disperse 26 g of the nanoscale calcium hydroxide prepared in step S3 in 59 mL of ethanol, ultrasonicate for 19 min to ensure the effect of dispersing nanoparticles, then continue to add 29 mL of the modified silane coupling agent solution prepared in step S4, and stir for 3 h; separate the modified nanoparticles by centrifugation, wash them with ethanol for several times, and then dry them at 69 ° C to obtain nanoscale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanoscale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0048] Comparative Example 6: Except that the silane coupling agent solution is used instead of the modified silane coupling agent solution in step S5, the remaining steps are the same as those in Example 3.
[0049] Comparative Example 7: Except that no modified silane coupling agent solution is added in step S5, the remaining steps are the same as those in Example 3.
[0050]
[0051] The wettability of the material was tested using an SDC-350 contact angle tester (Shengding Co., Ltd.). Table 1 shows the contact angle test data of the nano-scale anti-coagulation calcium hydroxide prepared in Example 3 and Comparative Examples 6 and 7. Analysis shows that compared with Comparative Examples 6 and 7, the material prepared in Example 3 has better hydrophilicity. The reason is that thanks to the special use of the modified silane coupling agent solution, the hydrophilic nano calcium hydroxide is easier to disperse in the aqueous system, not easy to agglomerate, and is conducive to forming a uniform suspension. And the hydrophilic surface is conducive to the interaction with water and other polar substances, improving the rate and efficiency of chemical reactions. In addition, hydrophilic surfaces usually have better biocompatibility and are suitable for the biomedical field. Used to prepare water-based coatings, cement and concrete to improve the water resistance and strength of materials. It can also be used to prepare bioactive materials, such as bone repair materials and drug carriers. Example 4
[0052] S1. Take 3.1 g of sodium dodecyl sulfate (SDS), 3.5 g of sodium lauroyl sarcosinate, 4.6 g of urea, 17 g of sodium hydroxide and 5.2 g of sodium carboxymethyl cellulose, dissolve them in 19 mL of ammonia water, 11 mL of ethylene glycol and 135 mL of deionized water, and ultrasonically treat them at 43 °C for 20 min to obtain an alkaline solution; the mechanical external force caused by ultrasound in this step is conducive to the rapid fragmentation and fusion of sodium dodecyl sulfate (SDS), sodium lauroyl sarcosinate and urea; the short vacuum microenvironment and precise temperature control caused by ultrasound are conducive to the rapid coating of sufficient hydroxyl groups on the fragmented drug surface, thereby ensuring a better role in the subsequent reaction process and promoting the rapid generation of nano-calcium hydroxide.
[0053] S2, 19 g Dissolve in 111 mL of deionized water, 42 mL of ethanol and 9 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 65 °C for 17 h to form a gel; the purpose of this step is to hydrolyze and condense the gel, ensure that the gel is uniform and has no obvious agglomeration, and promote the rapid formation of nano-scale calcium hydroxide. The purpose of ultrasonicating and stirring is to break the agglomerates that have been formed through the cavitation effect of ultrasound and redisperse the nanoparticles.
[0054] S3, the nanometer calcium hydroxide gel prepared in step S2 is dispersed in 150 mL of ethanol solvent, and after forming a uniform suspension, the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 4 mL / min, to ensure the stability and uniformity of the spray drying process, select a centrifugal nozzle, and atomize the liquid into fine droplets by high-speed rotation, set the inlet temperature to 223 ° C, the outlet temperature to 98 ° C, and dry quickly to obtain dry nanoparticles, and then use a cyclone separator to collect the dried powder, sieve the collected powder, remove large particles and agglomerates, ensure that the particle size of the powder is uniform, and then heat treat, calcine at 385 ° C for 3 h to remove organic matter, and obtain nanometer calcium hydroxide; finally, the collected powder is cooled to room temperature to avoid the influence of high temperature on the structure of the nanoparticles, and the dried nanometer calcium hydroxide powder is stored in a dry and cool place to avoid moisture and agglomeration. The purpose of this step is to atomize the dispersion into fine droplets by spray drying, dry quickly, and obtain dry nanoparticles. For the nano-scale calcium hydroxide gel, the spray drying method in this step can effectively maintain the dispersibility and morphology of its nanoparticles.
[0055] S4. Dissolve 9 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) in 59 mL of acetone, stir evenly, slowly add 12 mL of water, add 6.5 g of porphyrin calcium, continue stirring for 27 min, add 6 g of sodium citrate to adjust the pH value to 5.7 to promote hydrolysis and condensation reactions, heat the reaction mixture to 71 °C, and continue stirring for 4 h to obtain a modified silane coupling agent solution. The selection of porphyrin calcium in this step not only serves as a calcium supplement to provide sufficient Ca for the entire system 2+ In addition to ions, the molecules of calcium porphyrin are helpful to better support and disperse the nano-scale calcium hydroxide particles in the system.
[0056] S5, disperse 22 g of the nanoscale calcium hydroxide prepared in step S3 in 61 mL of ethanol, ultrasonicate for 22 min to ensure the effect of dispersing nanoparticles, then continue to add 27 mL of the modified silane coupling agent solution prepared in step S4, and stir for 3 h; separate the modified nanoparticles by centrifugation, wash them with ethanol for several times, and then dry them at 67 ° C to obtain nanoscale anti-coagulation calcium hydroxide. The purpose of this step is to form a protective film on the surface of the nanoparticles by the modified silane coupling agent, reduce the interaction force between the particles, and prevent agglomeration. The nanoscale calcium hydroxide described in the present invention should be stored in a dry and cool place to avoid moisture and agglomeration. When handling nanomaterials, appropriate protective equipment such as gloves, goggles and masks should be worn to avoid inhalation and contact with the skin.
[0057] Comparative Example 8: Except that ultrasonic treatment is not performed in step S2 but stirring is performed directly, the remaining steps are the same as those in Example 4.
[0058] Comparative Example 9: Except for replacing porphyrin calcium with porphyrin in step S4, the remaining steps are the same as those in Example 4.
[0059] Figure 6-Figure 8 The SEM images of the nano-scale anti-coagulation calcium hydroxide prepared in Example 4 and Comparative Examples 8-9 of the present invention are shown. It can be seen from the figure that the nano-scale anti-coagulation calcium hydroxide particles prepared in Example 4 of the present invention are uniform, while the particles of the materials prepared in Comparative Examples 8 and 9 are disordered and have poor dispersibility. It can be seen that porphyrin calcium and ultrasonic treatment are of great significance to maintaining the dispersibility of nanoparticles.
[0060] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, any other changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A nano-scale anti-coagulation calcium hydroxide, characterized in that: The specific preparation steps are as follows: S1. Dissolve 2.2-3.4 g of sodium dodecyl sulfate, 3.1-3.7 g of sodium lauroyl sarcosinate, 4.2-4.8 g of urea, 15-20 g of sodium hydroxide and 5.1-5.4 g of sodium carboxymethyl cellulose in 15-22 mL of aqueous ammonia, 8-13 mL of ethylene glycol and 125-145 mL of deionized water, and perform ultrasonic treatment at 40-45 °C for 20 min to obtain an alkaline solution. S2, 18-23 g Dissolve in 105-112 mL of deionized water, 33-45 mL of ethanol and 8-11 mL of ethylene glycol to form a precursor solution, slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol, and age the sol at 58-75 °C for 15-22 h to form a gel; S3, dispersing the nanometer-scale calcium hydroxide gel prepared in step S2 in 150 mL of ethanol solvent to form a uniform suspension, and then pumping the dispersion into the feed port of the spray drying equipment, controlling the feed rate to 3-5 mL / min, ensuring the stability and uniformity of the spray drying process, selecting a centrifugal nozzle, and atomizing the liquid into fine droplets by high-speed rotation, setting the inlet temperature to 121-235 ° C, the outlet temperature to 83-118 ° C, and quickly drying to obtain dry nanoparticles, and then using a cyclone separator to collect the dried powder, sieving the collected powder to remove large particles and agglomerates to ensure that the particle size of the powder is uniform, and then heat treating, calcining at 298-485 ° C for 2-4 h to remove organic matter to obtain nanometer-scale calcium hydroxide; S4, dissolve 8-11 g of γ-glycidyloxypropyltrimethoxysilane in 53-62 mL of acetone, stir evenly, slowly add 11-13 mL of water, add 5.8-6.7 g of porphyrin calcium, continue stirring for 25-30 min, add 5-7 g of sodium citrate to adjust the pH value to 5.5-6.2 to promote hydrolysis and condensation reactions, heat the reaction mixture to 63-75 ° C, continue stirring for 3-4 h, and obtain a modified silane coupling agent solution; S5. Disperse 19-27 g of the nanoscale calcium hydroxide prepared in step S3 in 55-67 mL of ethanol, and perform ultrasonic treatment for 10-30 min to ensure that the nanoparticles are dispersed. Then, add 22-34 mL of the modified silane coupling agent solution prepared in step S4, and stir for 2-4 h. Separate the modified nanoparticles by centrifugation, wash them with ethanol for multiple times, and then dry them at 60-80 ° C to obtain nanoscale anti-coagulation calcium hydroxide.
2. A nano-scale anti-coagulation calcium hydroxide according to claim 1, characterized in that: In the step S1, 2.8 g of sodium dodecyl sulfate, 3.5 g of sodium lauroyl sarcosinate, 4.6 g of urea, 19 g of sodium hydroxide and 5.4 g of sodium carboxymethyl cellulose are dissolved in 19 mL of aqueous ammonia, 11 mL of ethylene glycol and 135 mL of deionized water, and ultrasonically treated at 42 ° C for 20 min to obtain an alkaline solution.
3. A nano-scale anti-coagulation calcium hydroxide according to claim 1 or 2, characterized in that: In step S1, 2.2 g of sodium dodecyl sulfate, 3.6 g of sodium lauroyl sarcosinate, 4.2 g of urea, 20 g of sodium hydroxide and 5.4 g of sodium carboxymethyl cellulose are dissolved in 17 mL of aqueous ammonia, 11 mL of ethylene glycol and 135 mL of deionized water, and ultrasonically treated at 43 ° C for 20 min to obtain an alkaline solution.
4. A nano-scale anti-coagulation calcium hydroxide according to claim 1, characterized in that: In step S2, 19 g of Dissolve in 112 mL of deionized water, 39 mL of ethanol and 10 mL of ethylene glycol to form a precursor solution, and slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol. Age the sol at 70 °C for 19 h to form a gel.
5. A nano-scale anti-coagulation calcium hydroxide according to claim 1 or 4, characterized in that: In step S2, 21 g of Dissolve in 111 mL of deionized water, 37 mL of ethanol and 9 mL of ethylene glycol to form a precursor solution, and slowly add the alkaline solution prepared in step S1 while ultrasonicating and stirring to hydrolyze and condense the precursor to form a sol. Age the sol at 68 °C for 18 h to form a gel.
6. A nano-scale anti-coagulation calcium hydroxide according to claim 1, characterized in that: In the step S3, the nanometer-scale calcium hydroxide gel prepared in the step S2 is dispersed in 150 mL of ethanol solvent to form a uniform suspension, and the dispersion is pumped into the feed port of the spray drying equipment, and the feed rate is controlled to be 4 mL / min to ensure the stability and uniformity of the spray drying process. A centrifugal nozzle is selected to atomize the liquid into fine droplets by high-speed rotation, and the inlet air temperature is set to 215° C. and the outlet air temperature is set to 98° C. to perform rapid drying to obtain dry nanoparticles, and then a cyclone separator is used to collect the dried powder, and the collected powder is sieved to remove large particles and agglomerates to ensure that the particle size of the powder is uniform, and then heat-treated, calcined at 305° C. for 3 h to remove organic matter to obtain nanometer-scale calcium hydroxide.
7. A nano-scale anti-coagulation calcium hydroxide according to claim 1, characterized in that: In the step S4, 11 g of γ-glycidyloxypropyltrimethoxysilane (GPTMS) was dissolved in 53 mL of acetone, and after stirring evenly, 13 mL of water was slowly added, 6.7 g of porphyrin calcium was added, and stirring was continued for 30 min. 6 g of sodium citrate was added to adjust the pH value to 6.2 to promote hydrolysis and condensation reactions. The reaction mixture was heated to 74 ° C and stirred for 4 h to obtain a modified silane coupling agent solution.
8. A nano-scale anti-coagulation calcium hydroxide according to claim 1, characterized in that: In the step S5, 25 g of the nanoscale calcium hydroxide prepared in the step S3 is dispersed in 67 mL of ethanol, and ultrasonic treatment is performed for 22 min to ensure that the nanoparticles are dispersed. Then, 34 mL of the modified silane coupling agent solution prepared in the step S4 is added and stirred for 3 h. The modified nanoparticles are separated by centrifugation, washed with ethanol for multiple times, and then dried at 70 ° C to obtain nanoscale anti-coagulation calcium hydroxide.
9. The nanoscale anti-coagulation calcium hydroxide prepared according to any one of claims 1 to 8.
